Closing carbon cycles: Evaluating the performance of multi-product CO2 utilisation and storage configurations in a refinery. (January 2018) - Fernández-Dacosta, Cora; Stojcheva, Viktorija; Ramirez, Andrea
Highlights: Design of novel multi-product CO2 utilisation and storage configurations. Assessment of parallel and cascade CO2 utilisation systems. Multi-CCU(S) is a cost-effective climate change mitigation option for refineries. Feedstock replacement by CO2 is key to reduce emissions and improve business case. Abstract: Carbon capture and utilisation (CCU) has the potential to provide business cases as CO2 waste streams are turned into feedstock for the synthesis of marketable products. Although CCU could reduce fossil resource demand, its capability as a climate change mitigation option is under debate. In contrast to single-product CCU, this prospective study explores the techno-economic and environmental feasibility of novel systems that include more than one CO2 utilisation product. The combination of multi-product CCU with CO2 storage is also investigated. Two configurations have been designed, in which CO2 is captured in a refinery and converted into dimethyl ether (DME) and polyols, simultaneously ( parallel configuration) or in two consecutive cycles ( cascade configuration). Compared to a reference system without capture, results show that the largest direct CO2 emission reductions are achieved with CCS without utilisation (−70%) but at the expenses of higher total costs (+7%). Multi-product CCU systems show lower fossil depletion and costs than the reference without capture (−10% and −9%, respectively) because of feedstock replacement by the CO2 utilised. Combination of multi-product CCU with storage turns to be the best alternative for reduced climate change potential (−18% relative to the reference) while still been economically feasible. In addition to lower upstream emissions due to fossil feedstock replacement by utilising CO2, process direct emissions diminish owing to storage. No significant differences were found between the cascade and the parallel configurations. The extra effort to recycle CO2 in the cascade configurations is neither penalised nor rewarded.